Psychosocial repercussions in family dynamics after the end of treatment of cancerous tumors in boys and girls: differences between single parent families and biparental nuclear - Ramírez Zúniga, Karol (2019)
The present study emphasized as a main theme the psychosocial repercussions on family dynamics after the end of the treatment of cancerous tumors in boys and girls, this highlighting the differences between single parent families and biparental nuclear families. The methodology used was qualitative, specifically a retrospective study of phenomenological design which the information was obtained through interviews and was complemented with a scale (this only for the familism category). Subsequently, the analysis of the information was done using content analysis, the constant comparative method and the methodological triangulation of the information. Among the main conclusions: found were the open communication about the subject within the families, overprotection of the sick child, a greater tendency towards familism by the women of the nuclear families, temporary transfer of housing, the main caretaker mother, Religious beliefs as a resource to overcome with the situation, among others.